Protocol B - Induction of spawning and artificial fertilization [Pratical guide of protocols: broodstock management] - Basurco B.; Carrillo M.; Felip A.; Zanuy S.; Herráez M.P. (Advances in fish reproduction and their application to broodstock management: a pratical manual for sea bass, 2009)
Control of reproduction is an important issue in aquaculture for the success of farming production of the species under cultivation. It enables supplies of eggs and fry any time during the year and not just in the natural spawning time of the species. In the Mediterranean area and under culture conditions, sexual maturation in sea bass males is reached during the second year of life, although some males reach an early puberty near the first year of life. They are called early-maturing or precocious males. In contrast, females usually reach puberty near the third year of life. Moreover, sea bass breed normally under captive conditions and natural spawning occurs in the winter months (i.e. december-march). Furthermore, methods for inducing spawning in this species are available and they are commonly used in order to synchronize the production of eggs and sperm in mature fish. In fish, these methods are usually based on hormonal treatments, which act at the level of the pituitary gland releasing gonadotropin hormone, the luteinizing hormone (LH). This hormone modulates the control of many aspects of gonadal development, including oocyte growth and maturation, ovulation and spawning. This Protocol presents a general procedure applicable to male and female breeders for induction of spawning in sea bass by injection of LHRHa. The induction of spawning and artificial fertilization are two important issues in aquaculture to obtain gametes and fry for both experimental and commercial purposes.